SOME FEATURES OF AGREEMENT/DISAGREEMENT EXPRES¬SION IN SCIENTIFIC STYLE (Proceedings of Southern Federal University. Philology, 2013)
Makitova T. T.Keywords: scientific style, evaluative, agreement/disagreement, communicative function.The article is devoted to the study of some specific features of agreement/disagreement expressions in scientific style (on the material of monographs in the Humanities). The choice and organization of linguistic means of agreement/disagreement expression in different functional styles are not identical. They are defined by the communication situation and aims of communication. The article focuses on revealing peculiar features in expressing of agreement/disagreement conditioned by the factors mentioned above.